2013
DOI: 10.1021/bi401177n
|View full text |Cite
|
Sign up to set email alerts
|

Two Unique Phosphorylation-Driven Signaling Pathways Crosstalk in Staphylococcus aureus to Modulate the Cell-Wall Charge: Stk1/Stp1 Meets GraSR

Abstract: The Stk1/Stp1 and GraSR signal-transduction pathways are two distinct pathways in Staphylococcus aureus that rely on a reversible phosphorylation process in transducing external stimuli intracellularly. Stk1/Stp1 is an eukaryote-like Ser/Thr kinase phosphatase pair involved in purine biosynthesis, cell-wall metabolism, and autolysis. GraSR is a two-component system involved in resistance to cationic antimicrobial peptides. Both systems are implicated in S. aureus virulence and resistance to cell-wall inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 63 publications
2
70
1
2
Order By: Relevance
“…Cross-talk between Stk1/Stp1 and GraS/GraR signalling pathways was shown in S. aureus (Fridman et al, 2013). Stk1/Stp1 is a Hanks-type STK/phosphatase pair and GraS/GraR is a TCS which controls the resistance to cationic antimicrobial peptides.…”
Section: A Kalantari and Othersmentioning
confidence: 99%
“…Cross-talk between Stk1/Stp1 and GraS/GraR signalling pathways was shown in S. aureus (Fridman et al, 2013). Stk1/Stp1 is a Hanks-type STK/phosphatase pair and GraS/GraR is a TCS which controls the resistance to cationic antimicrobial peptides.…”
Section: A Kalantari and Othersmentioning
confidence: 99%
“…101 What is known is that GraR is another substrate of the S. aureus PASTA-containing eSTK Stk1. 102 By employing in vitro kinase reactions combined with tandem mass spectrometry analyses, Fridman et al show that GraR phosphorylation by Stk1 occurs on 3 threonine residues, namely Thr128, Thr130 and Thr149 102 (Fig. 5).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…Importantly, experiments reveal that these residues are required for efficient incorporation of D-ala into the bacterial cell wall, which could directly affect the efficiency of vancomycin binding and explain the GraR connection with vancomycin resistance. Additionally, the phosphorylation of these residues enhances the binding of GraR to the vraFG CAMP ABC transporter promoter to control its synthesis 102 (Fig. 4).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested that GraX as well as distinct two-component regulatory systems, such as VraSR and NsaSR, are also involved in S. aureus responses to antibiotics (21,22). Likewise, Stk1/Stp1 signaling appears to cross talk with GraSR in modulating S. aureus cell wall charge (23). GraSR may have special relevance to sensing peptide-based agents, including vancomycin (glycopeptide), daptomycin (lipopeptide), and structurally or functionally similar host defense peptides.…”
Section: Fig 3 Quantitative Mechanisms Of Hdps Againstmentioning
confidence: 99%